Understanding Singaporeans’ pro-environmental behaviors : a theoretical expansion of the influence of presumed media influence - Yang, Yanyi (2011)
Using the influence of presumed media influence (IPMI) model as the theoretical framework, this study aims to explain the influence of individuals’ attention to pro-environmental media messages on their pro-environmental behavioral intentions. Specifically, we examine both direct and indirect media effects on individuals’ pro-environmental behavioral intentions, and integrate the constructs of attitudes, descriptive, subjective, and injunctive norms into the model. Furthermore, we used the expanded model to examine the influences on three dimensions of pro- environmental behavioral intentions, namely energy conservation, recycling, and civic engagement. We tested the proposed extended framework on a random sample of 1,144 Singaporeans utilizing computer-assisted telephone interviewing (CATI).